Psychological Distress in Older Population with Diabetes Mellitus and Multicomorbidity: A Systematic Review - Aurellia Firstania; Eva Riantika Ratna Palupi; Fitri Handayani; Indra Gilang Pamungkas; Kristianto Dwi Nugroho; M Iqbal Angga Kusuma; Rahmawati Dian Nurani; Sartika Rajagukguk; Tsania Ayu Zaharany; Yusuf Hanafiah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Psychological distress in the elderly with diabetes mellitus and multiple comorbidities includes emotional responses such as stress, depression, and anxiety that arise due to the complex and prolonged demands of disease management. This study aims to analyze psychological distress in the elderly with diabetes mellitus and multiple comorbidities through a systematic review design according to PRISMA guidelines. Articles were obtained from four databases, namely Scopus, PubMed, EBSCO, and ScienceDirect, for the period 2020–2026. The selection was made based on consensus and assessed using the criteria of the Joanna Briggs Institute (JBI). Out of a total of 1,486 articles, 7 articles were obtained. The results of the study showed that psychological distress in diabetic patients was related to clinical factors, number of comorbidities, length of illness, and self-management ability. Multiple comorbidities have been shown to be the main determinants that exacerbate psychological distress in the elderly with diabetes. In addition, psychological distress has significant implications for self-management behaviors, which are an important component in diabetes control. The conclusion of the study confirms that psychological distress can no longer be viewed as a secondary condition, but rather as a primary component in the course of chronic disease that requires clinical attention in parallel with the physiological aspects in diabetic patients with multiple comorbidities.